Increased Creatinine Kinase Levels due to MDMA use without Myoglobinuria and Renal Failure - (:unkn) unknown (My University, 2012)
Akut ensefalopati ve serum kreatin kinaz yüksekliği ile başvuran adolesan hastalarda ekstazi kullanımın ayırcı tanıda akla gelmesi gerektiğini vurgulamak amacı ile çocuk acil polkliniğine 3,4- Methylenedioxymethamphetamine MDMA) ekstazi toksisitesine bağlı akut ensefalopati ile başvuran tetkiklerinde böbrek yetmezliği ve miyoglobinüri olmadan serumda kreatin kinaz yüksekliğespit edilen 15 yaşında erkek olgu sunulmuştur. (Marmara Üniversitesi Tıp Fakültesi Dergisi 2012;25:41-4)

We report a 15-year-old boy admitted to the pediatric emergency unit with acute encephalopathy associated with an elevated serum creatine kinase CK) level without myoglobinuria and renal failure, which was due to 3,4- Methylenedioxymethamphetamine (MDMA) toxicity and we emphasize hat especially in adolescents with acute encephalopathy and an increased erum CK level, ecstasy abuse should be kept in mind as a differential diagnosis. (Marmara Medical Journal 2012;25:41-4)
MDMA Kullanımı Sonrası Miyoglobinüri ve Böbrek Yetmezliği Olmadan Kreatin Kinaz Yüksekliği Olan Bir Olgu Sunumu
Keywords: Genel ve Dahili Tıp